Effect of steam frothing on milk microfoam: Chemical composition, texture, stability and organoleptic properties. (December 2022) - Klimanova, Yulia; Polzonetti, Valeria; Pucciarelli, Stefania; Perinelli, Diego Romano; Bonacucina, Giulia; Cespi, Marco; Gabrielli, Maria Gabriella; Santini, Giuseppe; Fioretti, Lauro; Cognigni, Luca; Vincenzetti, Silvia
Abstract: This study focuses on the evaluation of microfoam produced from processed dairy milk using the steaming function of the espresso machine as a function of temperature (30–80 °C), milk type (pasteurised or UHT), and whey protein contents. Foam characteristics, i.e., foam stability, viscosity, bubble size distribution noticeably varied depending on milk processing type and steam heating temperature. Foams made from pasteurised whole milk tended to be more stable. Bubbles in pasteurised milk foam were better distributed, especially at the temperature of 60 °C. It was observed that the optimal final temperature of steam frothing was in the range of 50 °C–60 °C. The results of sensory tests showed that consumers differentiated between the aroma and flavour of pasteurised and UHT milk, describing the degree of this difference from moderate to strong.